Childhood body mass index and perioperative complications - Olubukola O. Nafiu; Paul I. Reynolds; Olumuyiwa A. Bamgbade; Kevin K. Tremper; Kathy Welch; Joséphine Z. Kasa-Vubu (2007)
Summary Background: Our aim was to describe the incidence of quality assurance events between overweight/obese and normal weight children. Methods: This is a retrospective review of the quality assurance database of the Mott Children's Hospital, University of Michigan for the period January 2000 to December 2004. Using directly measured height and weight, we computed the body mass index (BMI) in 6094 children. Overweight and obesity were defined using age and gender‐specific cut off according to the National Center for Health Statistics (NCHS)/Centers for Disease Control and Prevention (CDC) (2000) growth charts. Frequency of quality assurance events were compared between normal weight, overweight, and obese children. Results: There were 3359 males (55.1%) and 2735 females (44.9%). The mean age for the entire population was 11.9 ± 5.2 while the mean BMI was 21.6 ± 6.7 kg·m −2 . The overall prevalence of overweight and obesity was 31.6%. Obesity was more prevalent in boys than girls ( P = 0.016). Preoperative diagnoses of hypertension, type II diabetes, and bronchial asthma were more common in overweight and obese than normal weight children ( P = 0.0001 for hypertension, P = 0.001 for diabetes and P = 0.014 for bronchial asthma). Difficult airway, upper airway obstruction in the postanesthesia care unit (PACU) and PACU stay longer than 3 h and need for two or more antiemetics were more common in overweight and obese than normal weight children ( P = 0.001). There was no significant difference in the incidence of unplanned hospital admission following an outpatient surgical procedure between normal weight and overweight/obese children. Discussion: Studies on perioperative aspects of childhood overweight and obesity are rare. Our report shows a high prevalence of overweight and obesity in this cohort of pediatric surgical patients. Certain perioperative morbidities are more common in overweight and obese than in normal weight children. There is a need for prospective studies of the impact of childhood overweight and obesity on anesthesia and surgical outcome.